Programmatic moderators of CBT correctional treatment for Whites and African Americans - Spiropoulos, Georgia Vassiliki (International journal of offender therapy and comparative criminology, 2018)
A recent experimental evaluation of a cognitive behavioral intervention (Reasoning and Rehabilitation) reported significantly greater reductions in recidivism for White male parolees than African American male parolees. These results prompted the present examination of whether specific program conditions may have differentially impacted program outcomes (returns to prison) for White (n = 141) and African American (n = 318) participants. Study participants were tracked for up to 33 months on parole. Discrete-time event history analysis tested for race interactions with the following program attributes: facilitator gender, facilitator race, number of facilitators, class size, and the facilitators’ evaluations of parolee participation on measures pertaining to level of participation, enjoyment, understanding, atmosphere and use of skills in the program. The gender of the facilitator, the number of facilitators, and sizes of the classes differentially affected success rates for African Americans compared with Whites. African American participants achieved more favorable outcomes with female facilitators than male facilitators, and when class sizes and the number of facilitators conformed to program guidelines. No statistically significant interaction effects were found for race of the facilitator, or facilitator evaluations of parolee participation.